Perancangan Aplikasi Sistem Penilaian Kinerja Karyawan Metode TOPSIS Berbasis Website - Ardiansyah, Fatur Rachman (Universitas PGRI Kanjuruhan Malang, 2023)
Technological advancements have a profound impact on various aspects of human life, including the world of work. The range of technologies used in work settings is extensive, ranging from simple to complex systems. However, many areas within the current scope of work have yet to fully embrace technological advancements. Recruitment, development, improvement, and evaluation processes are among those that can benefit from technology integration. At PT Sanjayatama Lestari, employee appraisals are still carried out manually, relying on supervisor assessments recorded in notes or word processing and number processing application files. These assessments may lack objectivity and transparency. This research aims to address the issue by designing a decision support system for employee evaluation at PT. Sanjayatama Lestari Surabaya. The waterfall method will be used to develop the application, utilizing a web-based programming language for user convenience and device compatibility. The application's design aims to enhance user experience, ensure valid data, and promote transparency in the employee evaluation process.